Evaluation of the Net Benefits of Using a Logistics Transportation Monitoring Application for PT. XYZ - Dimas Putri Pratiwi; Jarot S. Suroso (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: PT. XYZ is a telecommunications company that provides telecommunications network support and maintenance services. The company experienced disruptions in its logistics processes, resulting in losses equivalent to 60% of its total logistics costs. Because PT. XYZ had difficulty monitoring material deliveries, an information system in the form of a logistics transportation monitoring application was developed. However, the application has been operational for only six months. Infor mation systems (IS) have become an increasingly important field of study in business organizations because of the need to better understand the value generated by information and information technology. Objective: This study aims to evaluate the success and net benefits of PT. XYZ’s Logistics Transportation Monitoring Application. Methods: This study employed a quantitative approach by surveying 133 application users. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS to identify the factors influencing application use, user satisfaction, and net benefits. The DeLone and McLean Information Systems Success Model was used as the theoretical framework. Results: The hypothesis-testing results show that information quality and system quality have positive effects on user satisfaction. System quality and service quality positively affect application use, while user satisfaction and application use positively affect the net benefits of the Logistics Transportation Monitoring Application. Conclusion: The evaluation based on the DeLone and McLean Information Systems Success Model and PLS-SEM analysis using SmartPLS, with data from 133 respondents, shows that seven of the nine proposed hypotheses are supported. User satisfaction and application use are the primary drivers of the net benefits generated by the Logistics Transportation Monitoring Application.